An innovative method to produce green table olives based on "pied de cuve" technology. (September 2015) - Martorana, Alessandra; Alfonzo, Antonio; Settanni, Luca; Corona, Onofrio; La Croce, Francesco; Caruso, Tiziano; Moschetti, Giancarlo; Francesca, Nicola
Abstract: The technology of "pied de cuve" (PdC) is applied in food process only to produce wines with an enriched community of pro-technological yeasts. PdC promotes the growth of the desirable microbial strains in a small volume of grape must acting as a starter inoculums for higher volumes. The aim of the present work was to investigate the use of partially fermented brines, a technology known as PdC, developed with lactic acid bacteria (LAB) on the microbiological, chemical and sensory characteristics of green fermented table olives during two consecutive campaigns. The experimental plan included two trials based on different PdCs: trial A, PdC obtained with Lactobacillus pentosus OM13; trial B, PdC obtained through a spontaneous fermentation. Two control additional trials without PdC were included for comparison: trial C, spontaneous fermentation; trial D, direct inoculation of L. pentosus OM13. The use of PdCs favoured the rapid increase of LAB concentrations in both trials A and B. These trials showed levels of LAB higher than trial C and almost superimposable to that of trial D. Trial B was characterized by a certain diversity of L. pentosus strains and some of them dominated the manufacturing process. These results indicated PdC as a valuable method to favour the growth of autochthonous L. pentosus strains. Hierarchical cluster analysis (HCA) and principal component analysis (PCA) visibly discriminated olive processes fermented with the two experimental PdCs. Interestingly, on the basis of microbial and pH variables, both approaches showed that the olives produced with PdC technology are closely related to those of trial D, with the advantages of reducing the amount of starter to inoculate (trial A) and a higher LAB biodiversity (trial B). Volatile organic compound (VOC) composition and sensory analysis showed trials A and B different from the trials with no PdC added, in both years. Furthermore, the trial B showed the highest scores of green olive aroma and taste complexity. Spoilage microorganisms were estimated at very low levels in all trials. Undesired off-odours and off-flavours were not revealed at the end of the process. Highlights: This work describes an innovative technology to process green table olives. Pied de cuve technology allowed the rapid increase of lactic acid bacteria during processing. Pied de cuve determined the dominance of autochthonous Lactobacillus pentosus strains. This innovation strongly reduced the amount of commercial starter to be inoculated. The olive processed by Pied de cuve technology showed high sensory quality.